Caught in the loop: the role of volitional control in the FoMO and social media addiction cycle - Zhang, Yiheng (Frontiers in Psychology, 2025)
This study explores the bidirectional relationship between fear of missing out (FoMO) and social media addiction, with particular attention to the mediating role of volitional control. A total of 621 participants completed an online survey incorporating three validated instruments: the Bergen Social Media Addiction Scale (α = 0.974), the Trait-State Misplaced Anxiety Scale (α = 0.951), and the Volitional Control Questionnaire (α = 0.709). Following data cleaning, 88.71% of responses were retained for analysis. Using SPSS 26.0 and AMOS, descriptive statistics, hierarchical regression, and mediation analyses were performed. The results demonstrate a robust positive association between FoMO and social media addiction. FoMO was found to influence social media addiction both directly and indirectly via volitional control, whereas social media addiction affected FoMO only through direct pathways. Notably, volitional control partially mediated the effect of FoMO on social media addiction but did not mediate the reverse relationship. These findings offer valuable theoretical insights into the dynamic interplay between FoMO and social media addiction and suggest that strengthening volitional control may be key to developing effective interventions targeting problematic social media use.